Penerapan Program Care Each Other (Menerapkan Perilaku Hidup Bersih dan Sehat Pada Masa Pandemi COVID-19) di Panti Asuhan Aisyiyah DKI Jakarta - Pipin, Apriliana; Rohmah, Ulfa Nur; Utami, Ressa Andriyani; Efkelin, Ria; Ardiansyah (PPPM Stikes Banyuwangi, 2022)
Background: Inadequate sanitation facilities are closely related to the incidence of infectious diseases and poor personal hygiene in orphanages, especially during COVID-19.Conducting programs related to clean and healthy living habits can prevent the occurrence of other diseases. Objective: improve the knowledge and behavior of orphans in implementing clean and healthy living habits throughthe Caring for One Another program. Method: starts from the preparation phase, implementation in the form of health education, discussions and demonstrations through animated videos. rabbit; Result: Thisactivity expands participants' knowledge before andafter theCaring for One Another activity. Conclution: Delivering the Care Each Other program has proven effective in increasing knowledge and understanding of clean and healthy living habits through hand washing.